Vehicle-mounted net sampling of airborne Heteroptera (Hemiptera) in western Liberia, West Africa: 2. Tingidae, Nabidae, Aradidae, Lygaeoidea, Pyrrhocoridae, Alydidae, with bibliographical inventory - Krüger, Andreas (Zootaxa, 2019)
Notes on the heteropteran fauna in Liberia, their taxonomy and general distribution are reported for Tingidae, Nabidae, Aradidae, Blissidae, Cymidae, Lygaeidae, Ninidae, Rhyparochromidae, Pyrrhocoridae and Alydidae, collected by a vehicle-mounted net. Fourty-five species were discovered, 36 of which are new records for Liberia. Previously published country records for 31 species supplement the checklist. In addition, the following new taxa are described: Nabidae: Alloeorhynchus minutulus sp. nov.; Rhyparochromidae: Botocudo kpellensis sp. nov., B. liberiensis sp. nov., Mizaldus sylvaticus sp. nov..